POTENSI PRODUKSI DAN PROSPEK PENGEMBANGAN TANAMAN AREN (Arenga pinnata MERR) DI KALIMANTAN TIMUR - Mariati, Rita (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2013)
This study aimed to determine  1) the potential production of aren plant in Kalimantan Timur, (2) the development prospects  and processing industries  aren in Kalimantan Timur. The research was conducted  in the district of Kutai  Kartanegara, Kutai Barat,  and Kutai Timur. Data were collected on primary and secondary data. Sampling methods  purposive sampling  to farmers / producers of aren and a key information as many as 15 people. Data analysis was descriptive statistical analysis, and  SWOT analysis. The results showed that the aren plant in Kalimantan Timur spread over 7 districts  of  Kutai  Timur, Kutai Kartanegara, Kutai Barat, Samarinda, Penajam Paser Utara, Paser, and Bontang.  Counties with the largest aren plantation area is an area of Kutai Barat District 495 ha. Kutai Kartanegara regency area of 363 ha and the Kutai  Timur Regency area of 250 ha.  The district's largest producer of aren plantation in 2011 was as much of Kutai Timur Regency 76.62% of the total production of the aren plantation in Kalimantan Timur aren processing made by farmers / producers of aren in Kalimantan Timur are still confined to the traditional aren processing into brown sugar.  While processing aren into arenga palm sugar  and bioethanol  confined to trials. Effort is made by processing techniques and simple business management and packaging using banana leaf, mahang leaf, and plastic. Based on the SWOT analysis of the brown sugar  development strategies in Kalimantan Timur with 1 . Strategy is to turn around a. conduct intensive palm cultivation with improved varieties ; b. Provide access to capital for farmers / producer ; c . provide business management training ; d.Transfer technology palm cultivation and processing of the results of existing research . 2 . Devenif strategy is to : a. product diversification and modification of packaging ; b expand marketing network ; c. formed a joint venture group that fostered the related department . Model development is suggested to form a partnership with business groups